Preliminary study on cost analysis estimation and production yield of SMEs convection in Banyumas, Indonesia - Fauzan Romadlon; Firdayanthi Lestiana; Tslasa Audrey; Putri Rahmania; Putri Nur Faizah (Journal of Industrial Engineering and Management, 2023)
This preliminary study aims to compare the production capacity of the convection SMEs in Banyumas. The method used is quantitative, namely the cost estimation analysis and the Analysis of Variance (ANOVA) test, to calculate the statistical significance of production among the three SMEs. Based on the cost estimation analysis calculation, SME C has the highest production cost compared to SMEs A and B. The ANOVA test results significantly differ between the three convection SMEs' production capacity. The production capacity of SME B is higher than SME A and SME C. In practice, SME convection requires increasing production capacity, optimizing marketing strategies, and a product innovation approach to maintain business sustainability